Cell‐permeable high‐affinity tracers for Gq proteins provide structural insights, reveal distinct binding kinetics and identify small molecule inhibitors. (11th February 2020) - Kuschak, Markus; Namasivayam, Vigneshwaran; Rafehi, Muhammad; Voss, Jan H.; Garg, Jaspal; Schlegel, Jonathan G.; Abdelrahman, Aliaa; Kehraus, Stefan; Reher, Raphael; Küppers, Jim; Sylvester, Katharina; Hinz, Sonja; et al.
Abstract : Background and Purpose: G proteins are intracellular switches that transduce and amplify extracellular signals from GPCRs. The Gq protein subtypes, which are coupled to PLC activation, can act as oncogenes, and their expression was reported to be up‐regulated in cancer and inflammatory diseases. Gq inhibition may be an efficient therapeutic strategy constituting a new level of intervention. However, diagnostic tools and therapeutic drugs for Gq proteins are lacking. Experimental Approach: We have now developed Gq ‐specific, cell‐permeable 3 H‐labelled high‐affinity probes based on the macrocyclic depsipeptides FR900359 (FR) and YM‐254890 (YM). The tracers served to specifically label and quantify Gq proteins in their native conformation in cells and tissues with high accuracy. Key Results: FR and YM displayed low nanomolar affinity for Gαq, Gα11 and Gα14 expressed in CRISPR/Cas9 Gαq ‐knockout cells, but not for Gα15 . The two structurally very similar tracers showed strikingly different dissociation kinetics, which is predicted to result in divergent biological effects. Computational studies suggested a "dowel" effect of the pseudoirreversibly binding FR. A high‐throughput binding assay led to the discovery of novel Gq inhibitors, which inhibited Gq signalling in recombinant cells and primary murine brown adipocytes, resulting in enhanced differentiation. Conclusions and Implications: The Gq protein inhibitors YM and FR are pharmacologically different despite similar structures. The new versatile tools and powerful assays will contribute to the advancement of the rising field of G protein research.